Reforms and the Kerala Model - M A Oommen (Economic & Political Weekly January 12, 2008, 2008)
A model, which is not sustainable, is a tragedy. In the context of neoliberal reforms, this article raises certain emerging issues relating to equity and sustainability of the "Kerala model" of development.